2013
DOI: 10.1080/19393210.2013.843205
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins and ochratoxin A in maize of Punjab, Pakistan

Abstract: Aflatoxin and ochratoxin levels were determined in maize samples collected from store houses of 15 districts belonging to three agro-ecological zones of Punjab, Pakistan. Toxins were extracted by Aflaochra immunoaffinity columns and analysed by high-performance liquid chromatography (HPLC). Mean moisture content of maize kernels was recorded above the safe storage level of 15%. Results indicated that aflatoxin B1 and B2 contamination was found in 97.3% and 78.9% of the collected samples, respectively. Aflatoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
(18 reference statements)
2
5
0
Order By: Relevance
“…In another study conducted in Pakistan by Asi, Iqbal, Ariño and Hussain [39], higher levels of AFM 1 were documented in the winter season compared to the summer season, with significant difference ( p < 0.05). The present study results are in exact agreement with previous studies conducted in Pakistan [15,22,27,31,35,56], where they reported higher contamination of milk with AFM 1 in the winter season. The present study found high levels of AFM 1 contamination in milk samples collected in the autumn season (0.751 μg/L) after winter (0.875 μg/L); hence, the results are in agreement with those of Aslam, et al [57], who reported significantly higher AFM 1 levels in milk during the autumn season (2.60 μg/L).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In another study conducted in Pakistan by Asi, Iqbal, Ariño and Hussain [39], higher levels of AFM 1 were documented in the winter season compared to the summer season, with significant difference ( p < 0.05). The present study results are in exact agreement with previous studies conducted in Pakistan [15,22,27,31,35,56], where they reported higher contamination of milk with AFM 1 in the winter season. The present study found high levels of AFM 1 contamination in milk samples collected in the autumn season (0.751 μg/L) after winter (0.875 μg/L); hence, the results are in agreement with those of Aslam, et al [57], who reported significantly higher AFM 1 levels in milk during the autumn season (2.60 μg/L).…”
Section: Discussionsupporting
confidence: 93%
“…Hence, the Southern region is at the height of 400 ft, with a hot and dry climate, whereas the Northern region is around 2000 ft above the sea level and generally ambient and moist. The level of AFM 1 was highly correlated with the topography [35] of the country, as indicated by the findings that contamination (%) was the highest in the Northern region and kept on decreasing, moving through to the Southern region (Figure 2).…”
Section: Discussionmentioning
confidence: 93%
“…Likewise, AFB 1 and AFtotal in this study. These observations corroborate the findings of some previous researchers 63 , 64 , 66 , 82 . The co-existence of two or more fungi and their subsequent mycotoxin production in an environment suggests a possible non-antagonistic metabolite interaction, Moreover, the probable effect of combined exposure to aflatoxins with other mycotoxins in foodstuffs could be additive or antagonistic.…”
Section: Discussionsupporting
confidence: 93%
“…Makun et al 65 reported that samples of maize showed the highest levels of OTA were in the range of ND to 139.2 μg/kg in Nigeria. Conversely, Iram et al 66 did not detect ochratoxins in maize samples obtained from Punjab, Pakistan. Adebajo et al 67 also detected OTA in corn-based snacks in Nigeria only at toxicologically significant levels.…”
Section: Discussionmentioning
confidence: 92%
“…Aflatoxigenic and ochratoxigenic molds were isolated from maize and maize gluten meal samples from Faisalabad district of Punjab (Saleemi and others ). In a recent study, AFB 1 and AFB 2 occurrence was observed in 97.3% and 78.9% maize samples, respectively, collected from store houses in Punjab province (Iram and others ). Significant numbers of samples contained exceeding levels of AFB 1 and AFB 2 , but all samples were found free of AFG 1 , AFG 2 , and OTA.…”
Section: Mycotoxin Contamination Of Food and Feed In Pakistanmentioning
confidence: 96%